APPLICATION OF MODE SHAPE DATA BASE INDICATOR (MSDBI) FOR DAMAGE DETECTION OF STEEL FRAME BRIDGE STRUCTURE BASED ON MODAL ASSURANCE CRITERION (MAC) - Adhiyasa, Prima (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The substantial expansion of the global economy and the extensive urbanization witnessed in recent decades have rendered bridge infrastructure as a vital component of transportation systems. Conducting structural damage detection is a vital strategy to prevent structural failures and avert bridge collapse. One popular approach for detecting damage is to use mode shapes as characteristics in structural dynamics analysis. In this study, the identification of the mode shapes in the damaged condition will utilize the Modal Assurance Criterion (MAC), while the location of the damage within the simulation will be identified using the Mode Shape Data Base Indicator (MSDBI). The study was carried out with the help of a finite element model using Midas Civil software with a case study of a steel frame bridge. Referring to the report studied, damage identification focused on damage caused by loose bolts. The results of the analysis show that the MAC analysis has consistent values on mode shapes in each damage simulation with the mode shapes produced by the healthy condition model. Meanwhile, damage location is detected by the MSDBI index value in each damage simulation. It can be seen that the MSDBI index changes according to the location of the damage.